Study of the Edinburgh burgess community and its economic activities, 1600-1680 - McMillan, Joyce K. (University of Edinburgh, 1984)
While many histories of Edinburgh have been written, dealing with the architecture, folklore, culture, religion and politics of the city in the last five hundred years, little attempt has been made to chart the economic progress or to investigate the social structure of Scotland's capital. This thesis aims to illustrate the economic history of Edinburgh in the seventeenth century and to depict the urban' society of the period, largely through the exploits of its freemen, the burgess community. Edinburgh suffered its own particular disasters in a century whose middle years saw unprecedented national conflict. The accession of James VI to the English throne in 1603 removed the' Scottish king and court to London. The last visitation of bubonic plague to Scotland in 1645 removed anything up to one-third of the population of Edinburgh, its port of Leith and outlying suburbs. In addition, the city's role as capital of a rebellious kingdom ensured her twenty years of both physical turmoil and financial hardship, firstly at the hands of the Covenanters and secondly under the occupation of Cromwell. One question which should be asked, but can only be partially answered from the available research material, is - what effect did these incidents and intervals have on the economy of the city? Edinburgh was not noted as a manufacturing centre; its economic importance rested on trade and commerce. It is therefore to the merchants of the city that we should look for an insight into the economic condition of the burgh, and to a lesser degree, to the craftsmen, their socially inferior partners in the burgess community. The numbers, origins, status and social mobility of both groups have been studied, together with the sources and distribution of their wealth, in terms of goods, money, shipping and property. The impact of Edinburgh and its traders on other regions of Scotland has also been examined, and comparisons have been made, where possible, between the Scottish capital and the larger English towns. Finally, by using a variety of economic indicators, an impression has been pieced together of the economic progress of Edinburgh in the seventeenth century.
A study of the Edinburgh burgess community and its economic activities, 1600-1680
Keywords: History